In-Vitro Estimation of Total Phenolic, Flavonoid, Antioxidant Contents and Determination of Flavonoid, Amino Acid, and Vitamin Profiles of Ethanol Seed Extract of Annona squamosa Linn - Yakubu, Ojochenemi Ejeh; Audu, Jankada Patience; Adebisi, Arowora Kayode (African Journal of Biochemistry and Molecular Biology Research, 2024)
The aim of this research is to analyse the flavonoid, amino acid, and vitamin profiles of ethanol seed extract of Annona squamosa using high performance liquid chromatography (HPLC). The fruits of Annona squamosa were collected from Takum, Taraba State, the seeds were removed from the fruit washed with water, dried in the shade and then pulverized into fine powder. For the crude extraction, the method adopted by Yakubu et al. (2020) was adopted for this protocol. The IC50 of the seed was found to be 3.87. The total flavonoid content was significantly higher (182.76±0.61) compared with the total phenolic compound (70.34±3.04). A reliable detection and peak resolution were obtained from the HPLC analysis. The result showed the presence of nine amino acids, which include; Threonine (9.6%), Phenyl Alanine (17.0%), Aspartic Acid (26.0 %), Glutamic acid (16.0%), Leucine (5.7%), Iso-Leucine (5.3%), Glycine (5.0 %), Arginine (2.3), Glutamine (13.2%), three vitamins; vitamin K (0.4%), vitamin B1(63.0 %) and B3 (36.6%), and three flavonoid compounds Trolox (0.2%), Quercetin (2.1%) and Coumaric acid (97.7%) in plant sample. The phytochemical study confirms that the seed of Annona squamosa rich sources of amino acids such as and these herbal raw materials can exhibit a wide range of pharmacological activities.